Influence of noninstantaneous impulsive on null controllability of Atangana–Baleanu fractional stochastic differential equations - M. Elsaid Ramadan; Mahmoud M. El-Borai; Taher A. Nofal; Adel Darwish; Hamdy M. Ahmed (Journal of Inequalities and Applications)
Abstract This study explores the sufficient conditions for the null controllability of noninstantaneous impulsive Atangana–Baleanu fractional stochastic differential equations with Poisson jumps in a Hilbert space. Leveraging fractional analysis, compact semigroup theory, fixed point theorems, and stochastic analysis, we establish fundamental results that deepen the understanding of null controllability in complex stochastic systems. To demonstrate the applicability of our findings, we present a detailed example.